The Concept of Tolerance in a Multicultural Hadith Perspective (Analysis of the Quality Test of Sanad & Matan Hadith Sahih Muslim 1593) - Aprilita Hajar; Damanhuri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article will focus on the discussion of Hadith within the scope of multicultural, which is one of the existing multicultural values, namely around tolerance. There are several Hadiths that explain the importance of cultivating tolerance to deal with various differences. Because the Hadith is the second source of law after the Qur'an, it is necessary to analyze more deeply regarding the quality of the isnaad and its mat. Researchers using qualitative research methods, which refer to sources related to literature, it can be concluded that the explanation related to the command to respect the body, even though the body comes from the Jewish religion, it must still stand if the body passes by, because this is one of the forms of existing tolerance, and also respect for death itself. And there are many Isad in this Hadith that is Tsiqah, until it is concluded with Sahihul Isnad. And it can be concluded that the Hadith Sahih Muslim No. 1593 which discusses the chapter of the body, and related to this form of tolerance is Sahih.